Compound 19e, a Novel Glucokinase Activator, Protects against Cytokine-Induced Beta-Cell Apoptosis in INS-1 Cells - Oh, Yoon Sin; Seo, Eunhui; Park, Kaapjoo; Jun, Hee-Sook (Frontiers in Pharmacology, 2017)
Previously, compound 19e, a novel heteroaryl-containing benzamide derivative, was identified as a potent glucokinase activator (GKA) and showed a glucose-lowering effect in diabetic mice. In this study, the anti-apoptotic actions of 19e were evaluated in INS-1 pancreatic beta-cells co-treated with TNF-α and IL-1β to induce cell death. Compound 19e protected INS-1 cells from cytokine-induced cell death, and the effect was similar to treatment with another GKA or exendin-4. Compound 19e reduced annexin-V stained cells and the expression of cleaved caspase-3 and poly (ADP-ribose) polymerase protein, as well as upregulated the expression of B-cell lymphoma-2 protein. Compound 19e inhibited apoptotic signaling via a induction of the ATP content, and the effect was correlated with the downregulation of nuclear factor-κB p65 and inducible nitric oxide synthase. Further, 19e increased NAD-dependent protein deacetylase sirtuin -1 (SIRT1) deacetylase activity, and the anti-apoptotic effect of 19e was attenuated by SIRT1 inhibitor or SIRT1 siRNA treatment. Our results demonstrate that the novel GKA, 19e, prevents cytokine-induced beta-cell apoptosis via SIRT1 activation and has potential as a therapeutic drug for the preservation of pancreatic beta-cells.